1995
DOI: 10.1021/j100036a007
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure studies of the viscosity effects on the formation of the twisted intramolecular charge-transfer (TICT) state in 4,4'-diaminodiphenyl sulfone (DAPS)

Abstract: To investigate the dynamic solvent effects on the formation of the "twisted intramolecular charge-transfer (TICT)" state, the pressure as well as temperature effects on the fluorescence spectra of 4,4'-diaminodiphenyl sulfone (DAPS) in alcohol solvents were examined. It is concluded that solvent viscous friction makes an important contribution to the rate of TICT-state formation of DAPS in alcohols. The contribution of the dynamic solvent effect on the kinetics is well-separated from that of the intrinsic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…21 However, as has been quantitatively described in our previous paper, 13 the effect of the change in dielectric constant in a single solvent with pressure on ␣ is 6.2ϫ10 Ϫ2 -6.9ϫ10 Ϫ2 , 22 which is much less than the present experimental error. This fact is gauged by the intrinsic activation volume defined by the transition state theory ͑TST͒ (⌬V TST ), which involves the contribution of solvent polarity effect.…”
Section: ͑4͒mentioning
confidence: 48%
See 4 more Smart Citations
“…21 However, as has been quantitatively described in our previous paper, 13 the effect of the change in dielectric constant in a single solvent with pressure on ␣ is 6.2ϫ10 Ϫ2 -6.9ϫ10 Ϫ2 , 22 which is much less than the present experimental error. This fact is gauged by the intrinsic activation volume defined by the transition state theory ͑TST͒ (⌬V TST ), which involves the contribution of solvent polarity effect.…”
Section: ͑4͒mentioning
confidence: 48%
“…19,20 It is found that the TICT-state formation clearly exhibits a viscosity dependence, just as has been discussed based on the yield ratio measurements in the previous paper. 13 The important feature is that ln k CT decreases with ln , whose slope is in the order of 1-propanol Ͼ1-butanolϾ1-pentanol. Supposing a linear relationship, we attempted to apply the power law form for this viscosity dependence; …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations